Effect of Power and Mix Fuel Used Oil and Pertamina Dex on Exhaust Gas Emissions from Modified Diesel Engines - Sasmita, Aryo; Yohanes, Yohanes; Prilianto, Danuardi Restu (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2025)
Industrial growth and the increasing number of transportations cause the need for oil to increase. The increasing need for oil is directly proportional to the waste produced, namely used oil. Used oil waste can be a replacement fuel, which is produced quite large every year. This research used a mixture of used oil and Pertamina Dex used as a modified diesel engine fuel. The purpose of this study was to analyze the exhaust emissions produced by modified diesel engines. The research was conducted by varying the percentage of the mixture of used oil and Pertamina Dex, namely the percentage of a mixture of P10 (90% used oil and 10% Pertamina Dex), P20 (80% used oil and 20% Pertamina Dex) and P30 (70% used oil and 30% Pertamina Dex). Tests on the calorific value of fuel and exhaust emissions, which are varied based on the power load at idle (0 W), 1,000 W and 2,000 W. The test results showed that the calorific values of fuel P10, P20 and P30 were 44,191 kJ/Kg, 48,648 kJ/Kg and 50,074 kJ/Kg respectively. From this research it is known that the best fuel mixture of P30 with a loading power of 0 W, which emits a value of CO of 0.03%, CO2 of 2.32%, and HC of 34.86%. The results showed that the P10, P20 and P30 fuels met the exhaust emission quality standards according to the applicable regulations where the resulting opacity emissions did not exceed 40%.